Transnational Characters in Bhattarai's Muglan - Timalsina, Ramji (Dristikon: A Multidisciplinary Journal, 2022)
This article deals with the transnational characters used in Govinda Raj Bhattarai’s novel Muglan (1974). Based on the centuries long trend of Nepali people’s migration across the border and the pains they have been undergoing, the novel has presented three types of characters to show the types of Nepali transnational community living in India and Bhutan. The first type is that of transnational mobiles who leave Nepal for job and education, want to return to Nepal and cannot have any type of permanent settlement in the hostland. The main character Sutar is one of such characters. The highest number of characters in the novel is of this type. The second type of characters are diasporic ones who have left Nepal and have been permanently settled in Bhutan. Characters from the Nepali speaking community in Bhutan are of this type. The lowest number of characters in the novel are transnational outsiders who visit India from Nepal for a short time. The people who go for pilgrimage and cross-border purchase of everyday goods are the characters of this type. The discussion section of the article analyses the causes and effects of such migration resulting into the creation of such characters. The theoretical modality used for the analysis is Janine Dahinden and Steven Vertovec’s ideas of transnationalism. This article will be useful for the researchers and critics who want to study Nepali texts from transnational perspective.